Penerjemahan Tindak Tutur Direktif Bahasa Jepang dalam Novel Nijuushi No Hitomi dan Dua Belas Pasang Mata Karya Sakae Tsuboi - Pietasari, Vita Dyah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
The background of this research was based on the emerging common issue related to translation, which is the meaning shift from the source language to the target language as the result of the translation. The research focused on the translation of Japanese Directive Speech Act from the Japanese-language novel to Indonesian entitled Nijuushi no Hitomi and Dua Belas Pasang Mata written by Sakae Tsuboi. The purpose of this research is to describe the type of directive speech act, the translation technique used to translate, and the resulting translation quality. The findings of the research demonstrate that: (1) The type of Japanese-directive speech act found are: (a) requestives in the speech form of asking, inviting, and expecting, (b) questions, (c) requirement in the speech form of commanding and instructing, (d) prohibitives, (e) permissives in the speech form of allowing and letting, and (f) advisories in the speech form of advising and suggesting, (2) ten translation techniques, using single, couplet, triplet, and quartet variant. They are adaptation, amplification, borrowing, generalization, linguistic amplification, literal translation, modulation, particularization, reduction, and transposition that are used to translate the data, and (3) the quality of directive speech act translation in Sakae Tsuboi’s Nijuushi no Hitomi and Dua Belas Pasang Mata results in accurate, acceptable, and readable translation.